Protecting the right to identity against catfishing - Ndyulo, Lisa Neliswa Latima (Rhodes University, Faculty of Law, Law)
Catfishing is a form of impersonation occurring on social media that interferes with a person's right to identity. It involves creating a fake profile online using another person's images. The facets of the right to identity are image, name, and likeness, among others. Catfishing affects a person's right to identity and human dignity. Hence, the thesis aims to determine whether the right to identity adequately protects individuals against catfishing. This thesis is a desktop analysis considering the South African legal framework related to the right to identity, including the common law, the Constitution of the Republic of South Africa, 1996, and legislation. The thesis is also a comparative analysis assessing the adequacy of addressing catfishing through the right to identity. The study evaluates the right to identity's adequacy by juxtaposing the South African legal framework with California and Oklahoma's common law and statutory interventions. The study reveals that the right to identity protects South African social networking website users against catfishing. Like the common law right of privacy in California and Oklahoma, a person infringes the right to identity when they use another person's identity facets to portray them in a false light, and like the statutory right of publicity in California and Oklahoma, a person infringes identity when they appropriate facets of another person's identity for commercial gain. The infringement of the right to identity entitles a person to legal remedies, including a claim for damages, among other things. The thesis also considers principles of conflict of laws to determine the operative law in an instance where a victim resides in South Africa and the perpetrator resides in the US, or vice versa. The study recommends that developing the common law to recognise that identity can be infringed by mere appropriation not linked to a commercial purpose would be beneficial for addressing catfishing adequately in South Africa. Legal development contributes to the constitutional imperative to align the common law with society's shifting needs and address novel legal issues, such as catfishing.
Keywords: Catfishing -- South Africa; False personation Law and legislation -- South Africa; Torts -- South Africa; Mass media and publicity -- South Africa; Social media Law and legislation -- South Africa; Identity theft Law and legislation -- South Africa